2002
DOI: 10.1002/jmri.10214
|View full text |Cite
|
Sign up to set email alerts
|

Motion of the distal renal artery during three‐dimensional contrast‐enhanced breath‐hold MRA

Abstract: The observed cranial motion of the kidneys during a breath-hold adversely affects distal renal artery image quality on three-dimensional CE-MRA and jeopardizes reliable clinical evaluation. Shortening scan time may be beneficial for decreasing image degradation caused by this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 26 publications
1
41
0
Order By: Relevance
“…Blurring artifacts of the renal arteries are a known limitation of conventional MR angiographic acquisitions. Kidney motion propagates to the renal arteries when the patient starts breathing during relatively long MR examinations, and this can detrimentally affect the image quality for the renal arteries (30). It has been shown that the distal segments of the renal arteries move about 10-fold more than do the proximal segments during normal respiration (31).…”
Section: Discussionmentioning
confidence: 99%
“…Blurring artifacts of the renal arteries are a known limitation of conventional MR angiographic acquisitions. Kidney motion propagates to the renal arteries when the patient starts breathing during relatively long MR examinations, and this can detrimentally affect the image quality for the renal arteries (30). It has been shown that the distal segments of the renal arteries move about 10-fold more than do the proximal segments during normal respiration (31).…”
Section: Discussionmentioning
confidence: 99%
“…However, the previous iterations of this technique were limited in their ability to assess vessels in areas complicated by respiratory motion ( 16 ). Imaging the renal arteries requires a larger fi eld of view and is affected by motion from breathing ( 23 ). Mean renal artery movement during a breathing cycle has been reported to be 1.6 mm 6 1.9 in the proximal and 4.4 mm 6 2.8 in the distal renal arteries ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…While theoretical predictions suggest that greater improvement in FWHM may be obtained with longer scan times, such lengthening of time may not be appropriate for thoraco-abdominal CE-MRA acquisitions due to respiratory motion. Other factors, such as intrinsic motion of the renal arteries associated with cardiac pulsation and diaphragmatic drift during the breath-hold (39,40), may play an important role in limiting the achievable spatial resolution with CE-MRA, and other motion-compensated renal artery angiographic techniques may need to be evaluated (41)(42)(43)(44).…”
Section: Resolution Considerationsmentioning
confidence: 99%